A systematic review of intervention approaches for driving cessation in older adults. (9th February 2017) - Rapoport, Mark J.; Cameron, Duncan H.; Sanford, Sarah; Naglie, Gary
Abstract : Objective: The aim of this project was to review the literature on interventions aimed at facilitating driving cessation in older adults, with and without dementia. Methods: A literature search was performed using the databases MEDLINE, CINAHL, Cochrane Central, Embase, and PsycINFO, from 1994 to September 2014. Two independent raters screened articles for inclusion and extracted study data. We only included articles if they directly addressed the topic of intervention approaches to facilitate the process of driving cessation in older adults or to support the adaptation of older adults who have had to stop driving and included a control group. Results: Of an initial 477 unique records identified, 111 pertained to driving cessation in older adults, and only three articles were controlled trials of intervention approaches related to driving cessation. One article described an intervention for retired drivers with dementia, while another was aimed at caregivers of drivers with dementia, and the third included retired and retiring drivers without dementia. Outcomes such as reduced depressive symptoms, increased trips out of home, and efficacy in dealing with the driving cessation process were positive, but the specific outcome measures and magnitude of effects varied across studies. Conclusions: Although the results summarized in this review point toward potentially promising effects of interventions for facilitating driving cessation in older adults, these findings must be interpreted with caution given the significant methodological limitations of the studies, including small samples, participant attrition, lack of blinding, and non‐validated outcome measures. Copyright © 2017 John Wiley & Sons, Ltd.